Around 1948: The “Gentle Revolution” and Art History - Markowska, Anna (Artium Quaestiones, 2019)
Just like after World War I Italy experienced a transition from modernism to fascism, after World II Poland experienced a passage from modernism to quasi-communism. The symbol of the first stage of the communist revolution in Poland right after the war, the so-called “gentle revolution,” was Pablo Picasso, whose work was popularized not so much because of its artistic value, but because of his membership in the communist party. The second, repressive stage of the continued came in 1949–1955, to return after the so-called thaw to Picasso and the exemplars of the École de Paris. However, the imagery of the revolution was associated only with the socialist realism connected to the USSR even though actually it was the adaptation of the École de Paris that best expressed the revolution’s victory. In the beginning, its moderate program, strongly emphasizing the national heritage as well as financial promises, made the cultural offer of the communist regime quite attractive not only for the left. Thus, the gentle revolution proved to be a Machiavellian move, disseminating power to centralize it later more effectively. On the other hand, the return to the Paris exemplars resulted in the aestheticization of radical and undemocratic changes. The received idea that the evil regime was visualized only by the ugly socialist realism is a disguise of the Polish dream of innocence and historical purity, while it was the war which gave way to the revolution, and right after the war artists not only played games with the regime, but gladly accepted social comfort guaranteed by authoritarianism. Neither artists, nor art historians started a discussion about the totalizing stain on modernity and the exclusion of the other. Even the folk art was instrumentalized by the state which manipulated folk artists to such an extent that they often lost their original skills. Horrified by the war atrocities and their consequences, art historians limited their activities to the most urgent local tasks, such as making inventories of artworks, reorganization of institutions, and reconstruction. Mass expropriation, a consequence of the revolution, was not perceived by museum personnel as a serious problem, since thanks to it museums acquired more and more exhibits, while architects and restorers could implement their boldest plans. The academic and social neutralization of expropriation favored the birth of a new human being, which was one of the goals of the revolution. Along the ethnic homogenization of society, focusing on Polish art meant getting used to monophony. No cultural opposition to the authoritarian ideas of modernity appeared – neither the École de Paris as a paradigm of the high art, nor the folklore manipulated by the state were able to come up with the ideas of the weak subject or counter-history. Despite the social revolution, the class distinction of ethnography and high art remained unchanged.